Deciphering the electrochemical-mechanical coupling failure mechanism of Na-NASICON solid-state batteries - Wenwen Sun; Yang Li; Chen Sun; Xuanyi Yuan; Haibo Jin; Yongjie Zhao (Materials Futures)
Solid-state sodium metal batteries (SSMBs) have garnered significant attention for their high energy density and intrinsic safety, however, the sluggish kinetic and dendrite growth caused by solid-solid interfacial failure have severely constrained their practical applications. Understanding the structure-function relationships underlying the interfacial failure is therefore critical for guiding the design and modification of solid electrolytes. This work systematically investigates the electrochemical-mechanical synergistic failure mechanisms of NASICON-type Na _3 Zr _2 Si _2 PO _12 (NZSP) ceramic electrolyte at its interfaces with anode and cathode. The analysis reveals that the sodium-rich interfacial phase, formed from the reaction between NZSP and sodium metal, accelerates the pore formation and dendrite growth at the interface. Simultaneously, the decomposition products layer of the liquid electrolyte at the cathode/ceramic electrolyte interface significantly increases the resistance for sodium-ion transportation. Together, these factors contribute to the degradation of battery performance. The above findings not only make up for the lack of knowledge on the mechano-electrochemical correlation of interface failure in existing studies, but also provide a principle of cross-scale regulation for the design of long-life and high-performance NZSP-based SSMBs.